Virtual Reality Application of Interactive Interior: The Development Study for Computer and Android Smartphones - Hendro Trieddiantoro Putro; Luhur Sapto Pamungkas; Suparno Sastra; Murwantoro Panghargyo; Endang Setyawati; Endah Tisnawati (Universitas Atma Jaya Yogyakarta, 2022)
This research describes the process, obstacles, and results in making a Virtual Reality Application of interactive interior using Unity 3D. In this research, we propose a VR application that supports interaction and VR views between users and the digital environment using computers and android smartphones. The study has three stages, namely input, process, and output. C# script was developed for user interaction with the digital environment. The user can interact in a small interior room with digital objects such as moving around, changing furniture color, and switching the light on or off. The research successfully created a virtual reality application using Unity3D for computers and android smartphones. This study clearly describes the step of making virtual reality applications and the problems encountered during the process—also, a more stabilized method for developing the interactive user feature. Moreover, the research brings another opportunity for VR application development that focuses on other VR development factors such as immersion, imagination, and insight.